Values-Based Exercises for the Development of Reading Readiness Skills for Preschool Children - Salutin, May-Ar; Maguate, Guarin (International Journal of Scientific Research and Management (IJSRM), 2023)
This research paper is being prepared to develop and evaluate materials for the development of reading readiness skills of preschool children with emphasis on values necessary for their wholesome development, to provide readily made reading readiness materials which are beneficial to both the preschool teachers and the learners which they can use anytime in teaching and learning, and to address the dearth of instructional materials that focus on values formation among children as they acquire reading readiness skills. Five (5) peer evaluators and five (5) reading experts were selected to evaluate the values-based exercises for the development of reading readiness skills for preschool children. The responses of the study revealed the acceptability of the selections as to their content, presentation style, interest of pupils, as to whether the exercises are clear, and the development of basic reading skills for pre-school children are appropriate to their ages. The results of the analysis and interpretation of the responses revealed that the materials were found to be suited to the exercises provided for in the different levels.